Protein Binding of Glipizide Using Equilibrium Dialysis Technique: Effects of Hydrogen Ion Concentration, Drug Concentration and Ionic Strength - García, Javier J.; Ghaly, Evone S. (Puerto Rico Health Sciences Journal, 2013)
See manuscript